2017
DOI: 10.1038/s41698-017-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-focal sequencing of a diffuse intrinsic pontine glioma establishes PTEN loss as an early event

Abstract: Improved molecular understanding is needed for rational treatment of diffuse intrinsic pontine gliomas (DIPG). Here, using multi-focal paired tumor and germline exome DNA and RNA sequencing, we uncovered phosphatase and tensin homolog (PTEN) loss as a clonal mutation in the case of a 6-year-old boy with a diffuse intrinsic pontine glioma, and incorporated copy number alteration analyses to provide a more detailed understanding of clonal evolution in diffuse intrinsic pontine gliomas. As well, using the PedcBio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…Additionally, previous work from several groups has suggested that specific thresholds of replication stress may exists within different tumour populations that could exert important biological consequences for tumour development and growth and impact on further mutations/genetic alterations that facilitate tumour development [ 11 , 12 , 14 , 30 , 33 ]. Intriguingly, a recent report identified CNV gains and increased CDK18 mRNA expression in several distinct tumour populations from within a diffuse intrinsic pontine glioma, suggesting a selection preference for such genetic alterations to CDK18 expression during tumour development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous work from several groups has suggested that specific thresholds of replication stress may exists within different tumour populations that could exert important biological consequences for tumour development and growth and impact on further mutations/genetic alterations that facilitate tumour development [ 11 , 12 , 14 , 30 , 33 ]. Intriguingly, a recent report identified CNV gains and increased CDK18 mRNA expression in several distinct tumour populations from within a diffuse intrinsic pontine glioma, suggesting a selection preference for such genetic alterations to CDK18 expression during tumour development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data revealed a potentially important role for increased pAKT levels as a novel biomarker for predicting a reduced initial EGFR-TKI response in patients (26). Activation of AKT also predicted the development of diffuse intrinsic pontine gliomas based on the loss of PTEN (27). Nuclear pAKT (Ser473) Cyclin D1 WEE1 Bim Bcl-2 Bax Figure 1.…”
Section: Pakt As a Prognostic Marker In The Clinicmentioning
confidence: 91%
“…[94] PTEN is an established negative regulator of PI3K signaling and an important tumor suppressor, [95] with functional loss shown to be an early event in DIPG, [93] however, it is not regarded as a driver mutation. [93] This pinpoints the PI3K/AKT/mTOR signaling axis as the most common network controlling oncogenic growth and survival in H3K27M mutant DIPG ( Figure 2).…”
Section: Phosphoinositide-3 Kinase/protein Kinase-b/mammalian Target mentioning
confidence: 99%